Revisitando a Cuiabá e a Vila de Guimarães nos cantos e encantos de Hercule Florence (1827) - Martins, Deborah Pimenta (2018)
The proposal of this research is to revisit the cities of Cuiabá and Vila de Guimarães, from the reports of the traveler Antoine Hercule Romuald Florence, French artist, who came to Mato Grosso, in the 19th century, with the Expedition Langsdorff, and that, in 1827, held a provocative scientific survey, recorded in diary. In the reports, Hercule Florence reveals the "picturesque" and the "bright" of a fascinating Cuiabá, the various knowledges, the nature, the birds, the libertarian life of women, the (in)sensitivity with the pacu, fish "abundant" and "fat", and the religious traditions, and also reveals the physiognomy of the town of Guimarães. Hercule Florence reported the daily routine of "Scientific Expedition", in Mato Grosso, in the 19th century. With the aid of the historiography and discourse analysis, a world of feelings were embroidered in the patchwork of historical construction. The historiography - as the narrative of history that the historian produces - and discourse analysis, bringing the picture of "fat of pacu" on "bright" and "picturesque" of two cities found: Cuiabá and Vila de Guimarães.